Structural analysis of multi-storey buildings - Zalka, K. A. (Boca Raton : CRC Press, 2020)
"This book relies on creating continuum models for the structural analysis of multi-storey buildings and presents the theoretical background and the governing differential equations (for researchers) and simple closed-form solutions (for practicing structural engineers)"--
Includes bibliographical references and index.
Keywords: Tall buildings -- Design and construction; Structural analysis (Engineering)